Impaired bolus clearance in combined high-resolution esophageal manometry and impedance measurement helps to differentiate between esophagogastric junction outflow obstruction and achalasia - Zizer, Eugen; Seufferlein, Thomas; Hänle, Mark Martin (Zeitschrift für Gastroenterologie, 2017)
Introduction and aims High-resolution esophageal manometry (HRM) has improved the diagnostic work-up of esophageal motility disorders. Simultaneous evaluation of bolus clearance delivers useful information about the function of tubular esophagus. We assessed bolus clearance in a combined HRM-impedance examination for esophagogastric junction outflow obstruction (EGJOO) in comparison to achalasia patients. The collected data were assessed in a retrospective analysis.Patients and methods After gastroscopy excluded a mechanical esophageal or gastric obstruction, 142 consecutive patients underwent combined HRM-impedance examination. The assessment and interpretation of the manometry results were done according to the Chicago Classification of esophageal motility disorders v3.0. After classifying the motility disorder, the evaluation of bolus clearance was done according to published studies.Results All patients with achalasia (n = 24) showed a significantly impaired bolus clearance (< 80 %). Patients with unaffected peristalsis (n = 56) or patients with EGJOO (n = 14) each showed impaired clearance in 7 %, respectively. The evidence of axial hernia was not associated with impaired clearance.Conclusion Our results demonstrate a significant difference in impedance measurements between EGJOO and achalasia cases. This might be helpful as an additional tool to differentiate between achalasia and EGJOO patients. Furthermore, the role of the combined impedance-HRM investigation for early diagnosis of achalasia in “pre-achalasia” condition or in evaluation of potential progress of EGJOO to achalasia should be evaluated in a prospective study.
Keywords: Achalasie; Impedanzmessung; hochauflösende Ösophagusmanometrie; funktionelle Obstruktion